Omicron subvariants illustrate reduced respiratory tissue penetration, cell damage and inflammatory responses in human airway epithelia - Zaderer, Viktoria; Abd El Halim, Hussam; Wyremblewsky, Anna-Lena; Lupoli, Gaia; Dächert, Christopher; Muenchhoff, Maximilian; Graf, Alexander; Blum, Helmut; Lass-Flörl, Cornelia; Keppler, Oliver T.; Huber, Lukas A.; Posch, Wilfried; et al. (Frontiers in Immunology, 2023)
Introduction To explore whether the reported lower pathogenicity in infected individuals of variant of concern (VoC) Omicron and its current subvariants compared to VoC Delta may be related to fundamental differences in the initial virus-tissue interaction, we assessed their ability to penetrate, replicate and cause damage in a human 3D respiratory model. Methods For this, we used TEER measurements, real-time PCR, LDH, cytokine and complex confocal imaging analyses. Results and discussion We observed that Delta readily penetrated deep into the respiratory epithelium and this was associated with major tissue destruction, high LDH activity, high viral loads and pronounced innate immune activation as observed by intrinsic C3 activation and IL-6 release at infection sites. In contrast, Omicron subvariants BA.5, BQ.1.1 and BF7 remained superficially in the mucosal layer resulting merely in outward-directed destruction of cells, maintenance of epithelial integrity, minimal LDH activity and low basolateral release of virus at infection sites, as well as significantly smaller areas of complement activation and lower IL-6 secretion. Interestingly, also within Omicron subvariants differences were observed with newer Omicron subvariants BQ.1.1 and BF.7 illustrating significantly reduced viral loads, IL-6 release and LDH activity compared to BA.5. Our data indicate that earliest interaction events after SARS-CoV-2 transmission may have a role in shaping disease severity.